2019
DOI: 10.3390/en12132612
|View full text |Cite
|
Sign up to set email alerts
|

Gasification of Waste Cooking Oil to Syngas by Thermal Arc Plasma

Abstract: The depletion and usage of fossil fuels causes environmental issues and alternative fuels and technologies are urgently required. Therefore, thermal arc water vapor plasma for a fast and robust waste/biomass treatment is an alternative to the syngas method. Waste cooking oil (WCO) can be used as an alternative potential feedstock for syngas production. The goal of this experimental study was to conduct experiments gasifying waste cooking oil to syngas. The WCO was characterized in order to examine its properti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…The energy required to produce 1 kg of syngas or the energy per kilogram of treated feedstock is only reported by several researchers, Tamošiūnas et al [31][32][33] and Byun et al [30], respectively. Byun et al [30] reported the SER of 1.14 kWh per kilogram of MSW treated in the integrated demonstration gasification/vitrification unit for MSW, with a 10 tons/day capacity.…”
Section: Comparison Between Resultsmentioning
confidence: 99%
“…The energy required to produce 1 kg of syngas or the energy per kilogram of treated feedstock is only reported by several researchers, Tamošiūnas et al [31][32][33] and Byun et al [30], respectively. Byun et al [30] reported the SER of 1.14 kWh per kilogram of MSW treated in the integrated demonstration gasification/vitrification unit for MSW, with a 10 tons/day capacity.…”
Section: Comparison Between Resultsmentioning
confidence: 99%
“…The efficiency of the gasification process was calculated using Equations (1) Table 3 shows the results of the physicochemical analysis of raw sludge cake and sludge cake after HTC. Compared to other investigations on the thermal treatments of sludge, the carbon and volatile components and the heating value were high, which is good as a fuel for gasification [39,41]. In the case of proximate analysis, upon increasing the HTC temperature, fixed carbon increased due to carbonization, but volatile matter decreased due to thermal decomposition.…”
mentioning
confidence: 77%
“…η CGE is an index indicating the efficiency of converting thermal energy from a sample to a gas by gasification, and it can evaluate the energy recovery rate. In the case of η CCR , it is an index indicating the ratio of the carbon converted to gas to the carbon contained in the fuel, allowing the reactivity of the sample to be calculated; Y gas is an index for determining the amount of gas generation [39,40].…”
Section: Gasification Processmentioning
confidence: 99%
“…Therefore, the use of such crude biomass oils remain a longer-term possibility. Table 1 shows the typical composition of various bio-based feedctocks that can be used for co-processing in refineries [16][17][18][19][20][21][22][23][24][25][26].…”
Section: Feedstocks For Co-processingmentioning
confidence: 99%